Scanning electron microscopy of Chordodes moutoni Camerano, 1895 (Gordiida, Nematomorpha) - Zanca, Fernanda Mariel (2005)
Taxonomic characters of both male and female horse-hair worms Chordodes moutoni Camerano, 1895 (Nematomorpha) are re-described using scanning electron microscopy. The features are compared with the original description. C. moutoni cuticle has five different areolar types in male while female have six types of areoles. The crowned areoles, characteristic of Chordodes, are surrounded by other areoles forming pairs or clusters. Sexual dimorphism was found in the cuticular pattern, the female showing two different types of crowned areoles with distinct distribution pattern while the male has only one type of crowned areoles. These data are compared to other Chordodes species that have been studied.